Improving Life Skills in Sewing for the Independence of Female Students at the Al-Khoirot Gondanglegi Islamic Boarding School – Malang - Rohanita, Lailatur; Husni, Muhammad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Life skills are needed to develop independence, creativity, and innovation in the future. The research on the development of sewing skills at the Al Khoirot Gondanglegi Malang Girls' Islamic Boarding School aims to describe the concept of developing sewing life skills learning at the Al Khoirot Gondanglegi Malang Girls' Islamic boarding school, identify the stages of developing sewing skills learning, and analyze the factors that influence success or failure at the Al Khoirot Gondanglegi Malang girls' Islamic boarding school in developing sewing skills learning. This study uses a qualitative approach. Data were collected using interviews, observation, and documentation techniques. The data were analyzed using the Miles and Hubman analysis technique, which consists of data reduction, data display, and verification stages. The results of this study show the development process through the stages of introducing sewing learning media, understanding the basics of sewing safety, teaching basic techniques, reading fabric patterns and making sewing patterns, simple sewing exercises, introducing sewing terms and procedures, introducing creative design, mass production skills, business management training, collaboration with industry, marketing and sales programs. In the final evaluation, female students were able to produce independently sewn products that were worthy of sale, such as simple clothes, games, buns, and teacher uniforms. This study concluded that project-based sewing training is an effective method for developing life skills and increasing the independence of female students. Recommendations for developing product designs, marketing strategies, and partnerships with various parties are strategic steps to improve the quality and competitiveness of female students' work. In addition, personal branding and the use of social media, as well as participation in local exhibitions, are compelling opportunities to expand marketing reach and support the development of female students' potential in a sustainable manner.